A novel segmental challenge model for bleomycin-induced pulmonary fibrosis in sheep. (1st April 2015) - Organ, Louise; Bacci, Barbara; Koumoundouros, Emmanuel; Barcham, Garry; Kimpton, Wayne; Nowell, Cameron J.; Samuel, Chrishan; Snibson, Ken
ABSTRACT: Background: Idiopathic Pulmonary fibrosis (IPF) is a fatal respiratory disease, characterized by a progressive fibrosis and worsening lung function. While the outcomes of recent clinical trials have resulted in therapies to slow the progression of the disease, there is still a need to develop alternative therapies, which are able to prevent fibrosis. Aim: This study uses a segmental lung infusion of bleomycin (BLM) to investigate pulmonary fibrosis in a physiologically relevant large animal species. Methods: Two separate lung segments in eight sheep received two fortnightly challenges of either 3U or 30U BLM per segment, and a third segment received saline (control). Lung function was assessed using a wedged-bronchoscope procedure. Bronchoalveolar lavage fluid and lung tissue were assessed for inflammation, fibrosis and collagen content two weeks after the final dose of BLM. Results: Instillation of both BLM doses resulted in prominent fibrosis in the treated lobes. More diffuse fibrosis and loss of alveolar airspace was observed in high-dose BLM-treated segments, while multifocal fibrosis was seen in low-dose BLM-treated segments. Extensive and disorganised collagen deposition occurred in the BLM-treated lobes, compared to controls. Significant loss of lung compliance was also observed in the BLM-treated lobes, which did not occur in controls. Conclusions: Fibrosis comparable to IPF was induced into isolated lung segments, without compromising the respiratory functioning of the animal. This model may have potential for investigating novel therapies for IPF by allowing direct comparison of multiple treatments with internal controls, and sampling and drug delivery that are clinically relevant.